Interferência da dessecação, da época de colheita, do tratamento fungicida e do armazenamento na qualidade das sementes de girassol - Bernardes, Karlla Moraes (2008)
The present worked the interference of desiccation and harvest time on the quality of sunflower seed. The experiment was conducted in a commercial area, for production of hybrid Helio 251 sunflower seeds, for Helianthus of Brazil Company, in the municipal district of Conceição das Alagoas-MG, during the 2006/2007 crop. The experimental design was randomized blocks, with four repetitions. The treatments were distributed in a factorial outline (3 x 2), whose factors were three harvest times, with or without desiccation at physiologic maturation. The first harvest was done at the point of physiologic maturation of the seeds, observed in the field when 90% of the plants presented chapters with coloration bracts between yellow and chestnut brown, and approximately 30% humidity of the seeds. The second and third harvests were done between 10 and 20 days after the first one. The field was desiccated with paraquat herbicide (Gramoxone), for the first harvest. The harvested chapters were laid out on benches in a green house and thrashed manually after natural drying. The processing of the seeds was simulated with the aid of sieves and then stored in Kraft paper bags until the beginning of the tests, at environmental conditions. The evaluation of seed quality was done twice, the first are soon after the last harvest and the second one after 180 days of storage. The physiologic analysis of the seeds which were subjected to fungicide treatment was made in comparison with the non treated seeds, in the two storage times. The humidity of the aquenes at the moment of harvest and when reaching hygroscopic balance was measured, as well as productivity and weight of 1000 seeds. The physiologic quality of the seeds was evaluated through germination tests, seedling growth and emergency in sand. After data, collection and the confirmation of the presuppositions of normality and homogeneity, the analysis of variance was done and, subsequently, the bulked analysis. It was concluded that: a) desiccation of the field and harvest 20 days after natural drying gave seeds with the best quality; b) The fungicide treatment allowed seeds to better express the germination potential in laboratory; c) Physiological quality of seeds were reduced with storage.